1997
DOI: 10.1002/jlb.61.4.481
|View full text |Cite
|
Sign up to set email alerts
|

Defects in intracellular oxidative metabolism of neutrophils undergoing apoptosis

Abstract: Abstract:Apoptosis permits neutrophil recognition by macrophages, thereby not only limiting potential cytotoxicity but also promoting resolution of inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 47 publications
1
23
0
1
Order By: Relevance
“…Gustafsson et al 7) showed that PMA induces intracellular H 2 O 2 production and a rapid onset of apoptosis in human neutrophils. Narayanan et al 21) suggested that the onset of apoptosis in PMA-activated neutrophils is partly due to oxidative stress induced by down-regulation of the antioxidants superoxide dismutase and glutathione, which leads to intracellular accumulation of O 2 À , but the target molecule of O 2 À has remained to be identified. In the present study, we showed that PMA-induced cell death of mouse neutrophils was caspase-independent, A, PKC inhibitor GF109203X blocked PMA-induced phosphorylation of p38 MAPK.…”
Section: Discussionmentioning
confidence: 99%
“…Gustafsson et al 7) showed that PMA induces intracellular H 2 O 2 production and a rapid onset of apoptosis in human neutrophils. Narayanan et al 21) suggested that the onset of apoptosis in PMA-activated neutrophils is partly due to oxidative stress induced by down-regulation of the antioxidants superoxide dismutase and glutathione, which leads to intracellular accumulation of O 2 À , but the target molecule of O 2 À has remained to be identified. In the present study, we showed that PMA-induced cell death of mouse neutrophils was caspase-independent, A, PKC inhibitor GF109203X blocked PMA-induced phosphorylation of p38 MAPK.…”
Section: Discussionmentioning
confidence: 99%
“…Narayanan and colleagues [50] suggested that the onset of apoptosis in neutrophils is partly due to oxidative stress induced by down-regulation of the antioxidants superoxide dismutase (SOD) and glutathione, which leads to intracellular accumulation of …”
Section: Discussionmentioning
confidence: 99%
“…Conversely, when neutrophils reach a site of inflammation, apoptosis is delayed by inflammatory cytokines in the tissues, providing additional time for completion of the neutrophil's microbicidal function (8). However, neutrophils also become activated when they migrate from the blood; their subsequent production of ROS generates oxidative stress that instigates apoptosis (9,10). Redox-dependent mechanisms for apoptosis include the intracellular production of superoxide (O 2 . )…”
mentioning
confidence: 99%
“…Redox-dependent mechanisms for apoptosis include the intracellular production of superoxide (O 2 . ) and hydrogen peroxide (H 2 O 2 ) by activation of the NADPH oxidase in the granule pool (9) or the down-regulation of key antioxidant systems of the cell, such as superoxide dismutase (SOD), and a decrease in GSH (10). In addition, macrophages and phagocytic cells in the inflammatory area release Fas ligand during phagocytosis, contributing further to triggering apoptosis in neutrophils (11).…”
mentioning
confidence: 99%